Gold-Coated Superparamagnetic Iron Oxide Nanoparticles Functionalized to EGF and Ce6 Complexes for Breast Cancer Diagnoses and Therapy - Marcela Cândido; Paula Vieira; Andrea Campos; Cristina Soares; Leandro Raniero (Pharmaceutics, 2022)
Superparamagnetic iron oxide nanoparticles (SPIONs) have some limitations in the physiological environment, however, a modification on their surface, such as a core–shell structure with gold (SPIONs@Au), can enhance their applicability. In this study, SPIONs were synthesized by the chemical coprecipitation method, stabilized by sodium citrate, and followed by the gold-coating process. SPIONs@Au were functionalized with EGF-α-lipoic acid and chlorin e6 (Ce6)-cysteamine complexes, composing a Theranostic Nanoprobe (TP). The outcomes showed that the SPIONs@Au had changed in color to red and had an absorption band centered at 530 nm. The coating was verified in the TEM micrographs in bright and dark fields by EDS mapping, which indicated the presence of Au and Fe. The Ce6-cysteamine complex had a resonant band at 670 nm that enabled the diagnosis of biological samples using fluorescence analysis. In the measure of TNBC cell uptake, the maximum value of TP fluorescence intensity was obtained within 4 h of internalization. At 2 h, the incorporation of the TP in the cytoplasm as well as in the nuclei was observed, suggesting that it could be employed as a diagnostic marker. The PTT results showed significant percentages of apoptosis in the TNBC cell line, which confirms the efficacy of the TP.